Diagnostic Accuracy of Magnetic Resonance Imaging for International Federation of Gynecology and Obstetrics 2018 IB to IIB Cervical Cancer Staging: Comparison Among Magnetic Resonance Sequences and Pathologies. Issue 6 (18th November 2021) - Matsumoto, Yuka Kuriyama; Kido, Aki; Moribata, Yusaku; Chigusa, Yoshitsugu; Himoto, Yuki; Kurata, Yasuhisa; Otani, Satoshi; Yajima, Ryo; Nishio, Naoko; Kuwahara, Ryo; Minamiguchi, Sachiko; Mandai, Masaki; et al.
Abstract : Objective: This study aimed to investigate the most accurate magnetic resonance (MR) sequence for tumor detection, maximal tumor diameter, and parametrial invasion compared with histopathologic diagnoses. Methods: Fifty-one patients with International Federation of Gynecology and Obstetrics 2018 IB1 to IIB cervical cancer underwent preoperative MR imaging and surgical resection. Two radiologists independently evaluated the tumor detection, parametrial invasion, and tumor size in each of T2-weighted image, diffusion-weighted image, and contrast-enhanced T1-weighted image. Results obtained for squamous cell carcinoma (SCC) and adenocarcinoma were also compared. Results: Neither the tumor detection rate nor parametrial invasion was found to be significantly different among sequences. Tumor size assessment using MR imaging with pathology showed good correlation: r = 0.63–0.72. The adenocarcinoma size tended to be more underestimated than SCC in comparison with the pathologic specimen. Conclusions: Cervical cancer staging by MR images showed no significant difference among T2-weighted image, diffusion-weighted image, and contrast-enhanced T1-weighted image. Adenocarcinoma was prone to be measured as smaller than the pathologic specimen compared with SCC.